POWER SYSTEM STUDY ON INTEGRATING WIND AND PV POWER TO THE GRID SYSTEM - Abdalla Jobbara, Mohnad Ibrahim (Universiti Teknologi Petronas, 2013)
In the current century the demand of energy increased due to the industrial revolution and the high use of energy. PV and wind power were explored to meet the energy demand requirement. The objective of this research is to study and analyze the effects on the voltages and faults currents levels on the buses of the system when integrating wind and PV farms to the grid system. The grid system is IEEE industrial power system, modeling and simulation were implemented using DIgSilent software to perform power system studies of load flow and short circuit analysis on grid-connected at steady state condition to study the voltages and faults currents at the buses. From load flow analysis of PV integration to the industrial system, the voltage is improved at the Buses, the far the grid system from utility supply the more effective the improvement of Buses voltages. Integrating Wind farm to the grid system will affect on the voltage levels, increasing the power from the wind farm decreases the voltage on the system Buses. Short circuit analysis applied base on ANSI and IEEE standards and the comparison between the fault currents contribution of PV grid connected and wind grid connected system showed that the contribution of PV farm is higher than wind farm. The contribution is higher on the Buses near to the point of interconnection.